1972
DOI: 10.1002/jez.1401820110
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies on creatine kinase isozymes from skeletal‐muscle and stomach of trout

Abstract: Tissue-specific heterogeneity of creatine kinase (CPK) isozymes is particularly pronounced in various trout species. Several of the isozymes expressed in stomach and i n skeletal muscle appeared to be identical as judged by their electrophoretic behavior, but reversible dissociation studies on single, electrophoretically pure, CPK-isozymes isolated from these two tissues revealed significant differences between isozymes of similar electrophoretic mobility. Moreover, in contrast to trout skeletal muscle, the na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

1976
1976
1999
1999

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 19 publications
0
9
0
1
Order By: Relevance
“…This is not the first time that a heterogeneity of different creatine kinases has been found. It has been described in several reports on creatine kinases of various vertebrate species including human [28-301, rabbit [31,32] chick [33] and also trout [34,35]. As many separation techniques as studies have been carried out (starch gels, urea-starch gels, agarose gels, sodium dodecylsulphate/polyacrylamide gels and preparative isoelectric focusing) so that it is difficult to compare the different results with ours.…”
Section: Discussionmentioning
confidence: 91%
“…This is not the first time that a heterogeneity of different creatine kinases has been found. It has been described in several reports on creatine kinases of various vertebrate species including human [28-301, rabbit [31,32] chick [33] and also trout [34,35]. As many separation techniques as studies have been carried out (starch gels, urea-starch gels, agarose gels, sodium dodecylsulphate/polyacrylamide gels and preparative isoelectric focusing) so that it is difficult to compare the different results with ours.…”
Section: Discussionmentioning
confidence: 91%
“…USA 81 (1984) the brain (BB) isozyme in the electric organ has also been claimed (11). Furthermore, an additional species of CK exists in the trout (28). Two-dimensional gel electrophoresis unambiguously shows that the pCK-1 translation product comigrates with Torpedo muscle-specific CK subunit.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoglossidae and Cyprinidae), and all of the advanced teleosts, the B2 isozyme was restricted to the eye and brain. Previous work on fish creatine kinase isozymes had also indicated that at least three CK loci are present in diploid species (Champion & Whirr, 1976;Eppenberger et al, 1971;Perriard et al, 1972;SchoU & Eppenberger, 1971;Whitt et al, 1977).…”
Section: Creatine Kinase Lsozyme Evolutionmentioning
confidence: 99%